Serum selenium levels are associated with age-related cataract - Michał Post; Wojciech Lubiński; Jan Lubiński; Karol Krzystolik; Piotr Baszuk; Magdalena Muszyńska; Wojciech Marciniak (Annals of Agricultural and Environmental Medicine, 2018)
Objective The aim of the study is to analyse correlations between age-related cataract (ARC), serum selenium levels and glutathione peroxidase gene 1 and 4 (GPX-1 and GPX-4).